2007
DOI: 10.1113/jphysiol.2007.129833
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐dependent changes in temporal components of neurotransmission at the juvenile mouse calyx of Held synapse

Abstract: The temporal fidelity of synaptic transmission is constrained by the reproducibility of time delays such as axonal conduction delay and synaptic delay, but very little is known about the modulation of these distinct components. In particular, synaptic delay is not generally considered to be modifiable under physiological conditions. Using simultaneous paired patch-clamp recordings from pre-and postsynaptic elements of the calyx of Held synapse, in juvenile mouse auditory brainstem slices, we show here that syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
67
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 48 publications
10
67
0
Order By: Relevance
“…Thus, despite its size and security of transmission, the calyx-MNTB complex does not generate postsynaptic spikes that are invariant in amplitude and synaptic delay. A number of studies of the calyx of Held and MNTB in brain slices have reported similar phenomena (Borst et al, 1995;Klug and Trussell, 2006;Fedchyshyn and Wang, 2007).…”
Section: Intraspike Intervals and Peak Amplitudementioning
confidence: 67%
“…Thus, despite its size and security of transmission, the calyx-MNTB complex does not generate postsynaptic spikes that are invariant in amplitude and synaptic delay. A number of studies of the calyx of Held and MNTB in brain slices have reported similar phenomena (Borst et al, 1995;Klug and Trussell, 2006;Fedchyshyn and Wang, 2007).…”
Section: Intraspike Intervals and Peak Amplitudementioning
confidence: 67%
“…stimulation in vivo, significant activity-dependent changes in the transmission delay also occur at the mature calyx of Held (Fedchyshyn and Wang, 2007;Mc Laughlin et al, 2008;Tolnai et al, 2009). Thus, during high-frequency firing (Ͼ200 Hz), the retention of temporal precision of signal transmission might be limited even at the mature calyx of Held.…”
Section: Development Of Activity-dependent Plasticitymentioning
confidence: 99%
“…The properties of spiking have been shown to depend on previous activity (Fedchyshyn and Wang, 2007;Mc Laughlin et al, 2008;Lorteije et al, 2009;Tolnai et al, 2009). Usually, the last interspike interval (ISI) is used as the independent variable.…”
Section: Failures Of Ap Transmissionmentioning
confidence: 99%
“…6). Interestingly, a recent study found a frequency-dependent slowing of the EPSC rise time in fiber stimulation experiments (Fedchyshyn and Wang, 2007) that might be caused by the same mechanism. We interpret the slowing of the fast release component seen in Ca 2ϩ uncaging experiments as evidence for a preexisting heterogeneity of release kinetics among FRP vesicles.…”
Section: Mechanism Of Facilitation In the Depressed State Of The Synapsementioning
confidence: 99%